Enhanced nucleation of polypropylene by metal-organic frameworks (MOFs) based on aluminium dicarboxylates: influence of structural features - Mani, Mohan Raj; Chellaswamy, Ramesh; Marathe, Yogesh N.; Pillai, Vijayamohanan K. (RSC Advances, 2016)
Metal-organic frameworks (MOFs) based on aluminium dicarboxylates provide a new platform for the enhanced nucleation of isotactic polypropylene (iPP). For instance, aluminium dicarboxylates exhibit a unique butterfly-like structure similar to that of carboxylate-alumoxanes and correlates well with the nucleation characteristics of iPP. A subtle change in the structure of the ligand backbone (fumarate/succinate) does not alter the framework structure despite changing the hydrophilic/hydrophobic character and its subsequent nucleation characteristics. This suggests that the nucleating agent should facilitate favourable interaction with hydrophobic iPP for efficient nucleation. Further, a systematic variation of the alkyl chain length in the Al-dicarboxylate does not change the nucleation efficiency considerably, even though it increases the distance between the octahedral alumina chains in the metal-organic framework, suggesting that the butterfly-like structure present in the framework is a key aspect for nucleation. Finally, the significance of the orientational conformation of the dicarboxylate around the metal centre for the nucleation is confirmed by the poor nucleation efficiency of chromium and zirconium suberate MOFs where the orientation of suberate would be different from that of aluminium suberate due to the difference in the ligation of the carboxylate group. The present work thus provides valuable pathways for developing new nucleating agents based on MOFs with appropriate selection and orientation of the organic linkers around the metal centre.

Electrospun poly(3-hydroxybutyrate-co-3-hydroxyvalerate)/polyethylene oxide (PEO) microfibers reinforced with ZnO nanocrystals for antibacterial and antibiofilm wound dressing applications - Mahamuni-Badiger, Pranjali P.; Patil, Pooja M.; Patel, Pratikshkumar R.; Dhanavade, Maruti J.; Badiger, V. Manohar; Marathe, Yogesh N.; Bohara, Raghvendra A. (New Journal of Chemistry, 2020)
Biocompatible and biodegradable polymers are extensively used in designing wound dressing materials. The present investigation deals with the preparation of a unique blend of zinc oxide (ZnO) nanoparticles incorporated in poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV)/polyethylene oxide (PEO) microfibersviaan electrospinning technique for antibacterial, antibiofilm and wound dressing applications. This composite was prepared by incorporating previously synthesized ZnO NPs with better antibacterial and antibiofilm activity in PHBV-PEO (4 : 1) polymers in chloroform solution. Scanning electron microscopy (SEM) and Fourier transform infrared (FT-IR) spectroscopy confirmed that ZnO NPs were incorporated in the PHBV-PEO microfibers. The synthesized microfibers exhibited enhanced mechanical properties after the incorporation of ZnO NPs. The results of antibacterial and antibiofilm activity of the prepared microfibers revealed that the incorporated ZnO NPs in different concentrations (1%, 3%, and 5%) showed different degrees of antibacterial activity against pathogenic Gram-positiveStaphylococcus aureus(NCIM 2654) and Gram-negativePseudomonas aeruginosa(NCIM 5032), which are the main bacteria found in wound infections. The PHBV-PEO-ZnO microfibers exhibited excellent hemocompatibility with improved swelling behavior after the incorporation of ZnO NPs.In vitrocytotoxicity assays revealed the non-toxic nature of the prepared PHBV-PEO-ZnO microfibers. The current work confirms that utilizing a unique blend of the biodegradable, biocompatible, thermoplastic and hydrophobic natural polymer PHBV with hydrophobic, biodegradable, non-toxic and synthetic polymer PEO with ZnO NPs holds great potential for use as an antibacterial and antibiofilm material for wound dressing applications.